“Elektrotektif”: An Educational Game to Explore Electricity Concept Using Case-Based Learning - Muliyati, Dewi; Milenia, Rizka; Fahdiran, Riser (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
Learning physics is relevant to many cases in everyday life. Various media have been developed for physics learning, e.g., educational games. Educational games can be used as a way to motivate students who are mostly digital natives who were born and grew up in an all-digital environment. This research aims to produce a case-based educational game on electricity called Elektrotektif. This study used the research and development method with the ADDIE model. The result is an investigative game in which there are cases related to electricity in daily life, such as short circuits, electrocution, and electrostatic discharge. The quantitative evaluation results in a value of 86.5% for aspects validation of learning media, and the results from the user were 86%, with the interpretation “very good” to be used as learning companion media. Learning by using cases in a game can help students connect to real-world situations and provide solutions to physical events that excitingly occur around them.